Role of Artificial Intelligence in Remote Learning during COVID-19 Pandemic (Journal of Information Technology and Digital World, 2022)
This research paper offers the findings of a survey on much less researched regions of distance learning and studies during challenging situations for better schooling, all through the early COVID-19 pandemic (March-June 2020). The detailed assessment of Artificial Intelligence (AI) in education, the use of AI in education, typical learning in the pandemic era, and the role of artificial intelligence in disease outbreak learning, are all important for both current and future residents, according to the findings. In the week of May 28 to June 2, whilst many academic institutions throughout the United States had been in their term, 80% of parents residing with youngsters stated that their beginners had made the use of online assets while in lockdown. Prevailing situations and strain are associated with gaining knowledge during epidemics, in addition to a dyslexia prognosis. Results of the Household Pulse survey display that low-earning families now no longer get the right of entry to online instructional assets for distance learning on the equal fee as the better-earning families.
Keywords: Artificial Intelligence; dyslexia prognosis; COVID-19 pandemic; online instructional assets